Political support in hard times: Do people care about national welfare? - Jana Friedrichsen; Philipp Zahn (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2013)
During the Great Recession mass demonstrations indicated weakened political support in Europe. We show that growing dissatisfaction often reflects poor economic conditions and unemployment is particularly important. Using individual level data for 16 Western European countries for 1976-2010, we find that national economic performance matters even beyond personal economic outcomes. Finally, while the effects of growth and unemployment rates are the same across demographic subsets, the effect of inflation is heterogeneous. Well-educated or working individuals put a relatively higher weight on price stability than the less skilled or not working. Our findings reinforce the political importance of employment and growth policies.
Keywords: H11; O43; P16; 330; political support; satisfaction with democracy; growth; unemployment; collectivism